Aberrant tendinous chords with tethering of the tricuspid leaflets: a congenital anomaly causing severe tricuspid regurgitation. Issue 3 (13th February 2004) - Kobza, R; Kurz, D J; Oechslin, E N; Prêtre, R; Zuber, M; Vogt, P; Jenni, R
Abstract : Objective: To define the entity of tricuspid regurgitation caused by tethering of the tricuspid valve leaflets by aberrant tendinous chords. Design: Retrospective study. Setting: Tertiary care centre (university teaching hospital). Patients: 10 patients with unexplained severe tricuspid regurgitation. Methods: The last 13 500 echocardiographic studies from our facility were reviewed to identify patients with severe unexplained tricuspid regurgitation. Tethering was defined by the presence of aberrant tendinous chords to the tricuspid valve leaflets limiting the mobility of the tricuspid leaflet and resulting in incomplete coaptation and apical displacement of the regurgitant jet origin. Aberrant tendinous chords were defined as those inserting at the clear zone of the tricuspid leaflet and not originating from the papillary muscle. Patients fulfilling the diagnostic criteria for Ebstein's anomaly were excluded. Results: 10 patients with aberrant tendinous chords tethering one or more tricuspid valve leaflets were identified. There were short non-aberrant tendinous chords in seven patients, five of whom also had right ventricular or tricuspid annulus dilatation. Conclusions: Tethering of the tricuspid valve leaflets by aberrant tendinous chords can be the sole mechanism of congenital tricuspid regurgitation. It is often associated with short non-aberrant tendinous chords, which may develop secondary to right ventricular or tricuspid annulus dilatation. Awareness of tethering as a cause of tricuspid regurgitation may be important in planning reconstructive surgery.